(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This research examines the issue of emotional fatigue among physicians, including its symptoms and underlying reasons. The research that discovered emotional exhaustion syndrome in physicians and students across several disciplines formed the foundation of the article. The etiology, indicators, and manifestations of burnout within the medical profession. The article was predicated on research examining how physicians and students from various disciplines might recognize the symptom of emotional fatigue.